LAND-WATER RELATIONS IN THE KHANATE OF BUKHARA DURING THE SHAYBANI DYNASTY - Elbek Rasulov, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This article describes the reforms carried out by the rulers of the Shaybani dynasty for the development of important areas such as state economy, agriculture based on artificial irrigation, and trade.